Association between processed red meat intake and cardiovascular risk factors in patients with type 2 diabetes: a cross-sectional study from China - Zhang, Fan; Chai, Yongfei; Ren, Jiajia; Xu, Xiaoyu; Jing, Cuiqi; Zhang, Haimeng; Jiang, Yuhong; Xie, Hong (Frontiers in Nutrition, 2024)
Objective : To investigate the association between intake of Processed red meat (PRM) and risk factors for cardiovascular disease in patients with type 2 diabetes mellitus (T2DM). Methods : Diet survey, physical measurement and blood biochemical examination were carried out in T2DM patients. Subgroup analysis was conducted to investigate whether there were differences in correlation between PRM and CVD indicators. logistic regression model was used to analyze the relationship between PRM and abnormal risk of CVD risk factors. RCS was used to analyze the dose-response relationship between PRM intake and CVD risk factors. Results : Smoking had an effect modification on PRM intake and the risk of failing to reach FPG level control level; gender, smoking and drinking had an effect modification on PRM intake and the risk of abnormal SBP; gender had an effect modification on the association between PRM intake and abnormal DBP risk. Age had an effect-modifying effect on the association of PRM intake with abnormal TG index and HDL-C index (Pinteraction < 0.05). logistic regression showed that the OR with substandard HbA1c control in the highest PRM intake group was 1.620 times higher than that in the non-intake group, the OR with abnormal SBP control in the low PRM intake group was 1.025 times higher than that in the non-intake group, and the OR with substandard SBP control in the highest group was 1.166 times higher than that in the non-intake group. The OR of abnormal TG levels in the group with the highest intake of PRM was 1.095 times higher than that in the group without intake. The restricted cubic spline plot showed a nonlinear dose-response relationship between PRM intake and the risk of not achieving HbA1c and SBP control (P<0.05), and an atypical inverted U-shaped association between PRM intake and TC and LDL-C levels (P<0.05). Conclusion :The PRM intake in T2DM patients was generally low, but a nonlinear dose-response relationship was observed between PRM intake and the risk of substandard HbA1c and SBP control, and an atypical inverted U-shaped association was observed with TC and LDL-C levels.